PHYSICAL FITNESS AMONG CHILDREN AND ADOLESCENTS IN A COMMUNITY SPORT PROJECT - Santana, Fábio; Mota, Warley Otávio Alves da (International Journal of Movement Science and Rehabilitation, 2020)
Nowadays, there is a great concern in relation to the Physical Fitness of children and adolescents, since there is a growing wave of physical inactivity among them, which favors the early appearance of chronic degenerative diseases that increase over the years and that could be avoided. Thus, we aim to identify the levels of physical fitness among children and adolescents inserted in a Community Sports Project and compare the results between the male and female groups. The sample consisted of 139 children and adolescents aged 7 to 17 years old, inserted in a Community Sports Project through AABB Comunidade. To assess the components that are part of Physical Fitness, some tests were adopted from PROESP-BR (2016), where the following variables were evaluated: Body Composition, Flexibility, Muscular Endurance, Muscular Strength, Aerobic Capacity, Agility and Speed. The results were presented in percentages and in absolute values, being compared later between the male and female groups. Through the results obtained, the male group excelled the female group in all components, reaching a higher classification in all neuromotor tests. Regarding the distribution and body composition, the female group had a higher body mass index, as well as a greater accumulation of body fat. However, the groups presented average values ​​below that expected by the PROESP-BR classification, where there is a need to rethink sports practice and other factors that can interfere in the variables, so that these components can be improved, requiring further studies, especially , involving a control of classes with pre and post intervention assessment, contributing to the academic and scientific community.